Research ethics and diversity of worldviews: Integrated worlds and ubuntu - Moyra Keane (University of Johannesburg, 2021)
Many scholars have argued for inclusion of indigenous knowledges in all levels of teaching, as well as a re-thinking of research approaches in African and other southern contexts. However, methodology in indigenous knowledge research in southern Africa over the past few years shows only a few examples of an actual change in approach, genre, data collection or ethical considerations. This paper deals with just one of these aspects: research ethics. I argue that ethical considerations affect all aspects of the research process and hence affect how we construct and validate new knowledges. The paper aims to disrupt conventional ethical assumptions through illustrative research examples. It draws together three frameworks into a synthesised model to clarify different worldview perspectives that may be applied to research. The discussion and model may serve as an educational tool for researchers, particularly in the global South. I draw on both indigenous knowledge literature and three research projects located in rural South Africa to argue for the need to reconsider standard ethical norms. Standard ethical protocols are inadequate in providing guidance to students and researchers for complex contexts and diverse cultural values and indigenous worldviews.